Enhancing Childrens Cognitive Abilities Through â€œJelajah Alamâ€ Apllication : Promoting Well-being - Lely Ika Mariyati; Zaki Nur Fahmawati; Uce Indahyanti; Berlian Putri Pertiwi; Rolando Jordan Permana Putra (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
The use of technology in the early childhood learning process is rarely found despite the numerous benefits it offers. This study aimed to examine the effectiveness of the "Jelajah Alam" application in enhancing children's cognitive abilities. Research utilized quantitavive quasi-experimental : one sample pre-test post-test design. Research sample consisted of 19 kindergarten children selected through purposive sampling technique. Data measurement used was Nijmeegse Schoolbekwaamheids Testand Coloured Progressive Matrices Test. Data analysis use Wilcoxon signed-rank test. Findings revealed a significant difference between the pre-test and post-test score after implementing the "Jelajah Alam" application. Results indicated that the use of the application was effective in improving children's cognitive abilities. Results suggest that by playing â€œJelajah Alamâ€ application, enhance their cognitive ability based on their developmental phase. Result imply that by using technology, Parents and teacher have additional fun alternative to enhance their children cognitive ability.